The Evolution of Clause Structure in the Transition from Old English to Middle English - Khoiriyah, Mariyyatul; Hidayah, Meita Nur; Rahmaddani, Alya Nurul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The transition from Old English to Middle English was marked by significant changes in clause structure, affecting both syntax and grammatical patterns. This study analyzes how the reduction of inflectional morphology influenced word order, clause construction, and subordination strategies. As case markings declined in Middle English, sentence structure became increasingly reliant on fixed word order, resembling patterns found in Modern English. This shift was particularly evident in the transition from a relatively free word order in Old English to a more rigid Subject-Verb-Object (SVO) order in Middle English Additionally, the study explores the role of auxiliary verbs and conjunctions in compensating for the loss of inflectional markers. Using a descriptive and comparative approach, this research examines linguistic evidence from historical texts, comparing clause structures in Old and Middle English. The findings indicate that the loss of inflection led to shifts in syntactic strategies, including the increased use of periphrastic.constructions, modal verbs, and explicit subordinators to indicate clause relationships These findings contribute to a deeper understanding of how morphological changes impact syntactic evolution in the history of the English language and highlight the interplay between morphology and syntax in shaping linguistic structures over time.